FAKTOR-FAKTOR YANG MEMPENGARUHI CAKUPAN IMUNISASI DASAR LENGKAP PADA BAYI DI JORONG AUR JAYA NAGARI KOTO PADANG WILAYAH KERJA PUSKESMAS KOTO BARU TAHUN 2025 - Rahma Lia Frestami; Puja Maya Sari; Husna Husna (Ensiklopedia Research and Community Service Review, 2026)
Complete basic immunization is an important effort in preventing infectious diseases in infants. This study aimed to identify factors influencing complete basic immunization coverage among infants in Jorong Aur Jaya, Nagari Koto Padang, under the Koto Baru Public Health Center in 2025. The research employed a quantitative cross-sectional design. The population comprised all mothers with infants aged 9–18 months (n = 47), selected through total sampling. Data were analyzed using the chi-square test. Results showed significant correlations between maternal knowledge (p = 0.008), education (p = 0.009), and attitude (p = 0.000) with complete immunization status.Keywords: Infants, Complete Basic Immunization, Knowledge, Education, Attitude